Anticipated Property Tax Increases and the Timing of Home Sales: Evidence from Administrative Data - William H. Hoyt; Aaron Yelowitz (Center for Economic Studies and ifo Institute (CESifo), 2016)
Restrictions imposed on property assessment practices by state legislation such as Proposition 13 in California and Proposition 2 in Massachusetts can lead to significant divergences between the assessed and market values of property, particularly for households with long tenures. As properties are assessed at their market value when sold, this can lead to a significant divergence in the property tax payment for a current homeowner and a prospective purchaser of the property. This may lead to “lock-in”, decreased mobility, of homeowners reluctant to lose their tax advantage. Here using data on single family dwellings in Lexington, KY (Fayette County) we examine another practice leading to a systematic difference between assessed and market value of properties, the practice of assessing properties in individual neighborhoods on a four-year basis. In times of high housing appreciation, the difference in tax payments for houses last assessed two or three years earlier and their market values, the tax base for a new purchaser, can be significant and lead to a lock-in effect. Using administrative data from the Fayette County PVA we find evidence that housing sales are higher in the year before a neighborhood assessment suggesting that households adjust their mobility to capture the tax advantage associated with limited assessment.
Keywords: H20; H71; R30; 330; property taxation; assessment; lock-in